Initial Experience with the Use of Intravenous Eptifibatide Bolus during Endovascular Treatment of Intracranial Aneurysms - Yi, H.J.; Gupta, R.; Jovin, T.G.; Tayal, A.; Genevro, J.; Gologorsky, Y.; Horowitz, M. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Despite systemic heparinization, thromboembolic complications remain a major concern related to endovascular treatment of intracranial aneurysms. We assessed the safety of intravenous eptifibatide administered during aneurysm coiling procedures to prevent such complications.METHODS: From August 2001 to November 2004, 298 coil embolization procedures were performed to treat intracranial aneurysms; eptifibatide was used in 84 endovascular coil embolization procedures to treat 79 aneurysms in 74 patients. We retrospectively reviewed medical charts, radiographic images, and procedure notes to evaluate periprocedural complications related to eptifibatide.RESULTS: The mean age of the 74 patients in our cohort was 55 ± 9 years (range, 31–84) harboring 79 aneurysms (32 ruptured/47 unruptured). Eptifibatide was given prophylactically in 77 procedures, whereas in 7 procedures, it was given for treatment of a thromboembolic event (visualization of an arterial branch occlusion). A total of 5 (5.9% [total cohort]) bleeding complications related to eptifibatide occurred during 84 procedures. Two patients (2.4% [total cohort]/6.3% [ruptured group]) developed intracerebral hemorrhagic complications exacerbated by eptifibatide. The other 3 (3.6% [total cohort]) patients had groin hematomas requiring blood transfusions but had no surgical intervention. One thromboembolic event occurred in the 77 patients receiving eptifibatide prophylactically.CONCLUSIONS: Intravenous infusion of eptifibatide seems to be safe to administer in patients undergoing endovascular repair of an unruptured cerebral aneurysm. Caution must be used in patients harboring ruptured aneurysms as intracranial bleeding complications may occur. Further study is required to delineate the group of patients most likely to benefit from this therapy.